2018
DOI: 10.1038/s41598-018-27193-8
|View full text |Cite
|
Sign up to set email alerts
|

Swarming motility and biofilm formation of Paenibacillus larvae, the etiological agent of American Foulbrood of honey bees (Apis mellifera)

Abstract: American Foulbrood is a worldwide distributed, fatal disease of the brood of the Western honey bee (Apis mellifera). The causative agent of this fatal brood disease is the Gram-positive, spore-forming bacterium Paenibacillus larvae, which can be classified into four different genotypes (ERIC I-IV), with ERIC I and II being the ones isolated from contemporary AFB outbreaks. P. larvae is a peritrichously flagellated bacterium and, hence, we hypothesized that P. larvae is capable of coordinated and cooperative mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Swarming motility is related to biofilm formation, as the two processes are frequently co-regulated [52][53][54][55][56] . Biosurfactants have been frequently associated with bacterial motility, since for many strains swarming motility on semi-solid agar plates is dependent upon such compounds [57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…Swarming motility is related to biofilm formation, as the two processes are frequently co-regulated [52][53][54][55][56] . Biosurfactants have been frequently associated with bacterial motility, since for many strains swarming motility on semi-solid agar plates is dependent upon such compounds [57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…The EPS production and the biofilm formation by LAB could be an effective strategy against biofilms and colonization of pathogenic bacteria, since they compete with them for nutrients and space with different mechanisms of action [85][86][87][88][89][90][91][92]. Fünfhaus et al [93] showed that P. larvae were able to form biofilms at the beginning of the saprophytic phase, and this could promote optimal colonization of the honeybee larvae cadaver and the access to all nutrients. Several studies reported that some L. plantarum strains produce exopolysaccharides that, as well as contributing to biofilm formation, can exert an antimicrobial action [89,[94][95][96].…”
Section: Discussionmentioning
confidence: 99%
“…Honeybees ( Apis mellifera L.) are a key element in maintaining biodiversity and, moreover, provide ecosystem services (Fünfhaus et al ., 2018). Through pollination, insects are responsible for a global service worth $215 billion to food production (Goulson et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%